Sosialisasi Pemanfaatan Pekarangan Rumah Tangga sebagai Lahan Penanaman Tumbuhan Hortikultura dalam Rangka Mewujudkan Program Ketahanan Pangan di Desa Selaparang, Kabupaten Lombok Timur - Qothrunnada A.S.; Aluh Hanisa N.; Hariyadi (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Utilization of yards is one way to support the food security program launched by the Ministry of Agriculture. The Ministry of Agriculture developed the concept of intensive use of yards with the term "Sustainable Food Home Areas (KRPL)". The development of horticultural commodity types of vegetables is considered important both in terms of nutrition and economic value, especially in Selaparang Village, Suela District, East Lombok Regency. Selaparang Village is one of the villages whose livelihoods are mostly from the agricultural sector. This village is known for its commodities such as rice, tobacco, and secondary crops. This socialization activity is designed to provide information and education to the community to utilize the yard of the house as a supply area for commodities outside of the main commodities of Selaparang village such as vegetable plants to meet nutritional needs on a household scale. The people of Selaparang Village were given knowledge about how to plant plants in their yards and what plants can be planted. This socialization was held on January 5, 2023, held in the Selaparang Village Office Hall. The socialization method used was an interactive discussion with resource persons from the UPT Agriculture, Suela District. This socialization can optimize residents' knowledge about the use of yards as a land for planting Horticultural crops of vegetable types, so that they can be used as household scale food security.